Preclinical care of children with traumatic brain injury (TBI) - Sefrin, Peter; Brandt, Michael; Kredel, Markus (GMS German Medical Science, 2004)
The fact that injuries caused by accidents are the most common cause of death in children and adolescents in Germany gave rise to the study, which mainly deals with traffic accidents in this group. 200,221 records of emergency-service physicians in Bavaria which cover the period 1995-1999 were analysed with respect to the importance of traumatic brain injury (TBI) in children and adolescents (n = 721 - representing 45.8% of traffic injuries in this age group). The highest incidence of TBI was in summer (34.3%) and in the evening between 16.00 and 18.00 (23.7%). The time taken between accident and arrival of the emergency services was 8.8 ± 3.1 minutes. The preclinical phase lasted 19.3 ± 5.8 minutes. The probability of having an accident with TBI increases with age, the maximum being in the age-range 7 - 14 years (61.6%). Boys (63.2%) were almost twice as susceptible to injury as girls. 36.8% of all cases had no noticeable neurological disorder, 71.1% resulted in a Glasgow Coma Scale (GCS) score of 15. Only 6.3% had most severe neurological disorders, resulting in a GCS score of 3 - 5. Circulation parameters in the form of adapted hypotension were abnormal in only 3.4%, 21.9% of the children had a bradycardia and in 12.3% the blood oxygen saturation fell below 94%. The most frequent intervention was the laying of an i.v. line for infusions. 8.6% of the patients were intubated to allow for ventilation with oxygen. Analgesics were given in 16.7% of the cases. In 84.7% of all cases, the condition was stable and in only 3.3% was a severe deterioration to be observed. The assessments were made using both the National Advisory Committee for Aeronautics (NACA) and Glasgow Coma Scales (GCS). Discrepancies occurred, as a NACA scale of I - III and a GCS score of < 9 was reported in 4.9% of cases. In contrast a NACA scale of IV - VI was reported with a GCS score of 15 in 30% of all cases. TBI symptoms in children are less obvious than in adults, which leads to an age-dependent restriction in implementing therapeutic measures. If these restrictions are a result of misinterpretation of the situation or due to a lack of practice in the preclinical phase, then further training and education of the physicians involved in emergency service work are necessary.